Increasing the Ability of Psychological Testers in Counseling Guidance Students - Prisca Diantra Sampe; Junita Sipahelut; Neleke Huliselan; Izak Jakobis Makulua (CV. TOTUS TUUS, 2024)
The role of counseling and guidance professionals in modern education has become increasingly vital, particularly in addressing the diverse psychological and emotional needs of students. Among the critical competencies required for effective counseling is the ability to administer and interpret psychological tests, which are essential tools for assessing various psychological domains such as intelligence, personality, and emotional functioning. This study explores the significance of enhancing the skills of counseling guidance students as psychological testers, focusing on theoretical foundations, practical applications, and the need for targeted training programs. The study employed a quantitative approach, assessing participants' skills through a series of tests conducted during a two-day training session. The training aimed to bridge the gap between theoretical knowledge and practical application, offering students hands-on experience in administering and interpreting psychological tests. A total of 25 students participated in the training, and their performance was evaluated through written exams and practical tests. The results revealed that while most participants demonstrated a good understanding of the theoretical aspects, there were varying levels of proficiency in practical testing skills. The training proved effective in enhancing students' abilities, but it also highlighted the need for more structured and continuous practice to build confidence and competence. The findings suggest that targeted training programs are crucial for preparing counseling guidance students to meet the demands of their future professional roles. This study underscores the importance of investing in the professional development of counseling guidance students through comprehensive training programs. By equipping students with the necessary skills to administer and interpret psychological tests, these programs can improve the quality of counseling services and contribute to better psychological outcomes for individuals.